Hubungan Antara Konformitas dan Kohesivitas Remaja Laki-laki Anggota Komunitas Modifikasi Motor - Ahmad Mutamakin; Arundati Shinta; FX. Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2021)
Objective of this study is to explore the relationship between conformity and cohesiveness levels among adolesence boys. Those boys are member of a motorcycle modification community. It is likely a street boy gang. Their acitivities mostly are night illegally racing, touring and modificating their motorcycles. Indeed, modificating motorcycles are very expensive since they expect their motorcycles have amazing appearance. They do not have much money; therefore they have to become cohessive with other members. Their assistant to each other includes some parts of the motorcycles. And therefore, modificating their motorcycles would be much cheaper and easier. Underlying cohessive behavior is to conform. The boys’ conform behavior relates to their cohessive behavior (r = .588, p=.00).